Design and implementation of a VR environment aimed at enhancing the Social Anxiety Disorder’s (SAD) treatment. Evaluation of the sense of presence and immersion. : VRET - Pino, Olimpia; Squadroni, Luca; Borghese, Nunzio Alberto (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: We present here a novel approach to Virtual Reality Treatment (VRET) of Social Anxiety Disorders. It is based on a VR ecological scenario (that of a school room with desks), that can be personalized according to the actual fear level of the patient, adjusting the number of school mate that can be present together inside the room and the distance between the desks.Methods: We then conducted a user study to explore the sense of presence (Presence Questionnaire, PQ), immersive tendencies (Immersive Tendencies Questionnaire, ITQ), and subjective mental workload (NASA Task Load Index, TLX). The study evaluated 34 healthy students (average age: 24.558 years), of which 18 females.Results: Results from a usability trial are extremely positive. Our data suggests that participants liked mostly the high realism and sense of immersion of the Virtual Environment as well as the possibility to explore it widely. On the other side, the amount of workload of the task was evaluated very low, and therefore users can concentrate on the task.Conclusions: We conclude the article by discussing possible future directions for a large-scale pilot, that can lead to a solution that can be used at home to train under the guide and periodic supervision of a therapist (www.actabiomedica.it)